Leaving no one behind? Analysis of trends in access to water and sanitation services in the slum areas of Nairobi, 2003–2015 - Chikozho, Claudious; Kadengye, Damazo T.; Wamukoya, Marylene; Orindi, Benedict O. (Journal of water, sanitation, and hygiene for development, 2019)
Service provision backlogs in access to improved water and sanitation services remain a key barrier to the health and well-being of people living in Nairobi's slum areas. In this paper, we use quantitative data from the Nairobi Urban Health and Demographic Surveillance System to analyze the extent to which residents of Nairobi's slum areas have been able to access improved water and sanitation services from 2003 to 2015. This trend analysis reveals a slow but observable increase in access to improved sanitation facilities and garbage disposal services, while access to improved sources of water decreased. We conclude that the best scenario is the one in which all the three indicators have significantly improved during the period under consideration rather than having only some of them improving, while the others stagnate or decline. We recommend that Nairobi City Council and sector development partners refocus their attention towards increasing access to improved water and sanitation services in the urban low-income areas because lack of access to these essential services may expose people to waterborne diseases. It also threatens to leave behind a substantial number of people as the country moves towards the attainment of the water and sanitation-related sustainable development goals.